LANGUAGE SHOWERS IN PRIMARY MATHEMATICS EDUCATION - UHLÍŘOVÁ, Martina (Trends in education, 2016)
Language Showers (LS) are among the modern trends in education. Language Showers are based on the methodology of CLIL (Content and Language Integrated Learning). These activities subtly interconnect foreign-language lessons and non-language subjects. The paper is focused on the integration of Language Showers in teaching primary mathematics. The text lists the advantages and disadvantages associated with the implementation of Language Showers. We present a particular example of Language Showers and describe its implementation in the educational practice including the subsequent reflection.
Keywords: Language Showers; Primary school; Mathematics; Motivation.